Adhesive sheet for bonding transparent components and laminate

By using acrylic polymer and ferrous metal oxide in the adhesive sheet for transparent component bonding, combined with acid capture agent, the problem of the adhesive sheet fading under high temperature and high humidity conditions is solved, and the stability of the total light transmittance is achieved and Anti-decolorization effect.

CN115151618BActive Publication Date: 2024-12-20OJI HLDG CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202180014672.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-20
Filing Date
2021-02-18
Publication Date
2024-12-20
Estimated Expiration
2041-02-18

AI Technical Summary

Technical Problem

The existing transparent adhesive sheets are prone to fading under high temperature and high humidity conditions, which affects its service life and appearance quality.

Method used

The adhesive sheet for bonding with a transparent member containing an acrylic polymer and a ferrous metal oxide as the colorant is used to control the change in total light transmittance to be within 2%, preventing the fading of the adhesive layer, and combining an acid trapping agent to enhance the Anti-decolorization properties.

Benefits of technology

Store at 85°C and 85% relative humidity for 500 hours, and the total light transmittance change of the adhesive sheet is less than 2%, effectively preventing the fading of the adhesive layer, maintaining the coloring effect, and improving the durability of the adhesive sheet and Designability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115151618B_ABST
    Figure CN115151618B_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive sheet and a laminate for bonding transparent components, which can prevent fading (discoloration) when the adhesive sheet is used for bonding glass plates to each other and is placed under high temperature and high humidity conditions for a long time. The present invention relates to an adhesive sheet for bonding transparent components, which comprises an acrylic polymer and a colorant. In the adhesive sheet for bonding transparent components, the adhesive sheet is sandwiched between two glass plates, and when stored for 500 hours at 85°C and a relative humidity of 85%, the change in total light transmittance is less than 2%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet for laminating a transparent member and a laminate. Background Art

[0002] Previously, display devices such as liquid crystal displays (LCDs) and input devices used in combination with display devices such as touch screens have been widely used. In the manufacture of these display devices or input devices, transparent adhesive sheets are used for bonding optical components.

[0003] For example, Patent Document 1 discloses a double-sided adhesive sheet comprising a laminate including a flexible substrate layer, a first black layer and a second black layer, and a first adhesive layer and a second adhesive layer. In this case, the adhesive sheet used for laminating the black layer is sometimes required to have a design that does not impair the black appearance.

[0004] However, as a means for imparting a black appearance to an adhesive sheet, a method of adding a pigment to the adhesive sheet is also known. For example, Patent Document 2 discloses a black foil-shaped adhesive containing an adhesive component, a black pigment, and a styrene-maleic acid resin.

[0005] [Prior art literature]

[0006] [Patent Document]

[0007] Patent Document 1: Japanese Patent Application Publication No. 2005-060435

[0008] Patent Document 2: Japanese Patent Application Publication No. 2013-32430 Summary of the invention

[0009] [Problems to be solved by the invention]

[0010] As described above, black adhesive sheets obtained by adding black pigment to an adhesive layer are known, but when such adhesive sheets are used to bond glass plates together and then left for a long time under high temperature and high humidity conditions, fading (discoloration) of the adhesive layer sometimes occurs, which becomes a problem.

[0011] Therefore, in order to solve the problems of the prior art, the present inventors have conducted research for the purpose of providing an adhesive sheet that can be used to bond glass plates together and prevent fading (discoloration) when the adhesive sheet is left for a long time under high temperature and high humidity conditions.

[0012] [Technical means to solve the problem]

[0013] The inventors of the present invention have conducted extensive research to solve the above-mentioned problems and have found that by using an adhesive sheet to bond a transparent component containing an acrylic polymer and a colorant between two glass plates, the change in total light transmittance when stored at 85°C and 85% relative humidity for 500 hours is set to less than 2%. This prevents the adhesive layer from fading (discoloration) when the adhesive sheet is used to bond glass plates together and is then placed under high temperature and high humidity conditions for a long time.

[0014] Specifically, the present invention has the following structure.

[0015] [1] An adhesive sheet for bonding a transparent member, comprising an acrylic polymer and a colorant, wherein:

[0016] When the adhesive sheet for laminating a transparent member was sandwiched between two glass plates and stored for 500 hours in an environment of 85° C. and a relative humidity of 85%, the change in total light transmittance was less than 2%.

[0017] [2] The adhesive sheet for bonding a transparent member according to [1], wherein the colorant is a black metal oxide.

[0018] [3] The adhesive sheet for bonding a transparent member according to [1] or [2], wherein the total light transmittance is 30% or more and less than 85%.

[0019] [4] The adhesive sheet for bonding a transparent member according to any one of [1] to [3], further comprising an acid scavenger.

[0020] [5] The adhesive sheet for bonding a transparent member according to [4], wherein the acid scavenger is a compound having at least one selected from an oxazoline group and a carbodiimide group.

[0021] [6] The adhesive sheet for bonding a transparent member according to any one of [1] to [5], wherein the primary average particle size of the colorant is 0.01 μm or more and less than 5 μm.

[0022] [7] A laminated body comprising: a surface layer on one side of the pressure-sensitive adhesive sheet for laminating a transparent member according to any one of [1] to [6]; and a display body on the other side.

[0023] [8] The laminated body according to [7], wherein the surface layer is a glass layer or a resin layer.

[0024] [Effects of the Invention]

[0025] According to the present invention, it is possible to provide an adhesive sheet which can prevent discoloration even when the adhesive sheet is used for bonding glass plates together and is left for a long period of time under high temperature and high humidity conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram showing a cross section of an adhesive sheet having a release sheet.

[0027] [Explanation of Symbols]

[0028] 1: Adhesive sheet with peel-off sheet

[0029] 11: Adhesive sheet

[0030] 12a: Peel-off sheet

[0031] 12b: Peel-off sheet DETAILED DESCRIPTION

[0032] Hereinafter, the present invention will be described in detail. The description of the structural elements recorded below is sometimes based on representative embodiments or specific examples, but the present invention is not limited to such embodiments. Furthermore, the numerical range represented by "to" in this specification refers to the range including the numerical values ​​recorded before and after "to" as the lower limit and the upper limit.

[0033] (Adhesive sheet)

[0034] The present invention relates to an adhesive sheet for bonding transparent components, comprising an acrylic polymer and a colorant. Here, the adhesive sheet for bonding transparent components is sandwiched between two glass plates, and the change in total light transmittance when stored for 500 hours at 85°C and 85% relative humidity is less than 2%. The adhesive sheet of the present invention is preferably an adhesive sheet for bonding transparent components, and the transparent components are optical components. That is, the adhesive sheet for bonding transparent components of the present invention is preferably an adhesive sheet for bonding optical components.

[0035] The adhesive sheet for laminating transparent components of the present invention (hereinafter, also referred to as an adhesive sheet) has the above structure, so when the adhesive sheet is used for laminating glass plates to each other and then placed for a long time under high temperature and high humidity conditions, the fading (discoloration) of the adhesive sheet can also be prevented. In the adhesive sheet that suppresses fading (discoloration) in the above manner, the coloring caused by a colorant or the like can be maintained for a long time. Therefore, the adhesive sheet for laminating transparent components of the present invention can be an adhesive sheet for use under high temperature and high humidity conditions, and can also be an adhesive sheet for use under conditions of 85°C or above and a relative humidity of 85% or above.

[0036] Previously, when glass plates were laminated on both sides of an adhesive sheet with a colorant and the laminate was placed under a high temperature and high humidity environment for a long time, it was seen that the adhesive sheet faded. In particular, this phenomenon is significantly visible when a metal oxide is included as a colorant. Therefore, the inventors set the change in the total light transmittance of the adhesive sheet to less than a specified value by controlling the various compositions or manufacturing conditions of the adhesive sheet containing a colorant (metal oxide). It is thus found that fading (decolorization) can also be suppressed in the adhesive sheet containing a colorant (metal oxide) in the present invention, and coloring using a colorant (metal oxide) can be maintained even under a high temperature and high humidity environment.

[0037] In addition, the inventors and others have also found out that when an adhesive sheet with a colorant is placed under high temperature and high humidity conditions (for example, above 85°C and relative humidity above 85%) for a long time (for example, more than 500 hours) and glass plates are bonded to both sides of the adhesive sheet, the adhesive sheet will fade. Furthermore, the fading of the adhesive sheet of the present invention is the following phenomenon: even when the adhesive sheet with a colorant is placed only under high temperature conditions above 85°C, or when the adhesive sheet with a colorant is placed under prescribed conditions of a relative humidity of more than 85% for a long time (for example, more than 500 hours), it will not be found when a resin film or the like is bonded to at least one side of the adhesive sheet. In this way, the present invention has found out that when an adhesive sheet is placed under high temperature and high humidity conditions (for example, above 85°C and relative humidity above 85%) for a long time (for example, more than 500 hours) and glass plates are bonded to both sides of the adhesive sheet, the adhesive sheet will fade, thereby successfully suppressing this fading phenomenon.

[0038] In this specification, the change in total light transmittance of an adhesive sheet can be calculated by placing an adhesive sheet (laminated body) with glass plates bonded to both sides in an environment of 85°C and 85% relative humidity, and measuring the total light transmittance before and after 500 hours. The change in total light transmittance is a value calculated by the following formula.

[0039] Change (%) = (total light transmittance of the laminate before treatment at 85°C and 85% relative humidity) - (total light transmittance of the laminate after treatment at 85°C and 85% relative humidity)

[0040] The amount of change in total light transmittance is preferably less than 2%, more preferably 1.8% or less, further preferably 1.5% or less, and particularly preferably 1.2% or less.

[0041] In this specification, the discoloration resistance of the adhesive sheet can be evaluated by placing the adhesive sheet (laminated body) with glass plates on both sides in an environment of 85°C and 85% relative humidity, and the change in L* value after 500 hours. The change in L* value is a value calculated by the following formula.

[0042] Change = (L* value of the sample before treatment) - (L* value of the sample after treatment)

[0043] The amount of change in the L* value is preferably less than 1.0, more preferably 0.9 or less, and still more preferably 0.8 or less.

[0044] Furthermore, in the present invention, when the adhesive sheet is attached to a display showing a black screen, etc., its design can be improved. Specifically, when the adhesive sheet of the present invention is attached to a display showing a black screen, the black color rendering degree of the display (the preferred degree of black color rendering degree) can be improved, thereby improving the design of the display and the display device having the display. In addition, even if the display is in a state where a black screen is not displayed, the black color rendering degree of the display is improved by attaching the adhesive sheet, thereby emphasizing the sense of unity with the surroundings and improving the design.

[0045] The total light transmittance of the adhesive sheet (laminate) with glass plates bonded to both sides before treatment at 85°C and relative humidity of 85% is preferably less than 85%, more preferably less than 80%, and further preferably less than 75%. The total light transmittance of the laminate before treatment at 85°C and relative humidity of 85% is preferably more than 30%. In addition, the total light transmittance of the laminate after the adhesive sheet (laminate) with glass plates bonded to both sides is placed in an environment of 85°C and relative humidity of 85% for 500 hours is preferably less than 85%, more preferably less than 80%, and further preferably less than 75%. The total light transmittance of the laminate after treatment at 85°C and relative humidity of 85% is preferably more than 40%. By setting the total light transmittance of the laminate within the range, the black color rendering degree of displays, etc. can be more effectively improved.

[0046] Furthermore, the total light transmittance of the adhesive sheet (laminate) with glass plates bonded to both sides is a value measured by the following method. First, the adhesive sheet (laminate) with glass plates bonded to both sides is treated in an autoclave at 40°C and 5 atmospheres for 30 minutes. Then, the total light transmittance of the laminate is measured according to Japanese Industrial Standards (JIS) K 7150. The measurement is performed three times and the average value is set as the total light transmittance of the laminate. Furthermore, the determination of the total light transmittance can be performed using, for example, an integrating sphere light transmittance measuring device (manufactured by Nippon Denshoku Industries, NDH-5000). Furthermore, the total light transmittance of the adhesive sheet (laminate) with glass plates bonded to both sides is the same value as the total light transmittance of the adhesive sheet, so the total light transmittance of the adhesive sheet (laminate) with glass plates bonded to both sides is set as the total light transmittance of the adhesive sheet.

[0047] The lower limit of the haze of the adhesive sheet is not particularly limited, and is preferably 0.1% or more, for example. In addition, the haze of the adhesive sheet is preferably 30% or less, more preferably 25% or less, further preferably 20% or less, and particularly preferably 15% or less. By setting the haze of the adhesive sheet within the above range, the black color rendering degree of a display or the like can be more effectively improved.

[0048] In the adhesive sheet of the present embodiment, the product of the total light transmittance of the adhesive sheet and the haze value is preferably 300 or less, further preferably 250 or less, further preferably 200 or less, and particularly preferably 170 or less. Furthermore, the lower limit of the product of the total light transmittance of the adhesive sheet and the haze value is not particularly limited, but if the haze and total light transmittance for optical purposes are considered, it is preferably 10 or more. Among them, it is preferred that the total light transmittance of the adhesive sheet is 40% or more and the haze is 6% or less, and it is preferred that the total light transmittance of the adhesive sheet is 90% or less and the haze is 0.1% or more. By setting the product of the total light transmittance and the haze value to the range, and setting the total light transmittance and the haze of the adhesive sheet to the specified range, the black color rendering degree of the display, etc. can be more effectively improved, and the visibility of the display, etc. can also be more effectively improved.

[0049] The thickness of the adhesive sheet is preferably 10 μm or more, more preferably 20 μm or more, and more preferably 50 μm or more. In addition, the thickness of the adhesive sheet is preferably 5000 μm or less, more preferably 3000 μm or less, and more preferably 1000 μm or less. By setting the thickness of the adhesive sheet to below the upper limit, water vapor can be prevented from penetrating from the end to improve durability. On the other hand, by setting the thickness of the adhesive sheet to above the lower limit, the handling of the adhesive sheet can be made easier.

[0050] The adhesive sheet of the present invention can be a single-layer adhesive sheet. In addition, the adhesive sheet can be a single-sided adhesive sheet including a substrate (preferably a transparent substrate) on a single side, or a double-sided adhesive sheet. As a double-sided adhesive sheet, there can be listed: a single-layer adhesive sheet comprising an adhesive layer, a multi-layer adhesive sheet with multiple adhesive layers stacked, a multi-layer adhesive sheet with other adhesive layers stacked between the adhesive layer and the adhesive layer, a multi-layer adhesive sheet with a support stacked between the adhesive layer and the adhesive layer, and a multi-layer adhesive sheet with an adhesive layer stacked on the single side of the support and other adhesive layers stacked on the other side. In the case where the double-sided adhesive sheet has a support, it is preferred to use a transparent support as the support. As a support, a general film used in the optical field in the same manner as a transparent substrate can be used. This double-sided adhesive sheet is also excellent in transparency as an adhesive sheet as a whole, and therefore can be suitable for the connection of transparent components to each other.

[0051] like Figure 1As shown, the present invention may also relate to an adhesive sheet with a release sheet, which includes a release sheet 12a and a release sheet 12b on both surfaces of an adhesive sheet 11. Examples of the release sheet include a release laminate having a release sheet substrate and a release agent layer provided on one side of the release sheet substrate, or a polyolefin film such as a polyethylene film or a polypropylene film as a low-polarity substrate.

[0052] The release sheet substrate in the release laminate can be paper or polymer film. In optical applications, polymer film can be preferably used to prevent the mixing of foreign matter. As the release agent constituting the release agent layer, for example, a general-purpose addition type or condensation type silicone release agent or a compound containing a long-chain alkyl group can be used. It is particularly preferred to use a highly reactive addition type silicone release agent.

[0053] Specific examples of silicone-based release agents include BY24-4527 and SD-7220 manufactured by Toray Dow Corning Silicone Co., Ltd. or KS-3600, KS-774, and X62-2600 manufactured by Shin-Etsu Chemical Co., Ltd. In addition, it is preferred that the silicone-based release agent contain a silicone-based release agent having a SiO2 unit and a (CH3)3SiO 1 / 2 Unit or CH2=CH(CH3)SiO 1 / 2 The organosilicon compound having a unit is a silicone resin. Specific examples of the silicone resin include BY24-843, SD-7292, SHR-1404 manufactured by Toray Dow Corning Silicone Co., Ltd. and KS-3800, X92-183 manufactured by Shin-Etsu Chemical Co., Ltd.

[0054] As the releasable laminated sheet, commercially available products may be used, for example, a heavy release film made of a polyethylene terephthalate film subjected to a release treatment manufactured by Teijin DuPont Films Co., Ltd. or a light release film made of a polyethylene terephthalate film subjected to a release treatment manufactured by Teijin DuPont Films Co., Ltd.

[0055] In the case where the adhesive sheet of the present invention is a double-sided adhesive sheet, it is preferably a pair of release sheets having different release forces. That is, in order to facilitate peeling, the release sheets are preferably configured so that the release properties of one release sheet and the other release sheet are different. If the release property of one release sheet is different from the release property of the other release sheet, it is easy to peel off only the release sheet with high release property first.

[0056] The gel fraction of the adhesive sheet of the present invention is preferably 30% to 100%, more preferably 40% to 100%, and even more preferably 50% to 100%.

[0057] (Adhesive composition)

[0058] The adhesive sheet of the present invention contains an acrylic polymer and a colorant. The adhesive sheet of the present invention preferably further contains an acid scavenger.

[0059] (Acrylic polymer)

[0060] The acrylic polymer is not particularly limited as long as it contains acrylic monomer units, and preferably contains non-crosslinkable (meth)acrylate units (a1) and acrylic monomer units (a2) having a crosslinkable functional group. In the present specification and claims, "unit" refers to a repeating unit (monomer unit) constituting a polymer.

[0061] The non-crosslinking (meth)acrylate unit (a1) is a repeating unit derived from an alkyl (meth)acrylate. Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, stearyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0062] Among the alkyl (meth)acrylates, at least one selected from methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, n-dodecyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate is preferred in terms of improving adhesion.

[0063] The acrylic monomer unit (a2) having a crosslinkable functional group is preferably at least one selected from a carboxyl group-containing monomer unit, a hydroxyl group-containing monomer unit, an amino group-containing monomer unit, and a glycidyl group-containing monomer unit. That is, the acrylic polymer preferably has at least one crosslinkable functional group selected from a carboxyl group, a hydroxyl group, an amino group, an amide group, a glycidyl group, and an isocyanate group.

[0064] Examples of the carboxyl group-containing monomer unit include acrylic acid and methacrylic acid.

[0065] The hydroxyl-containing monomer unit is a repeating unit derived from a hydroxyl-containing monomer. Examples of the hydroxyl-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxypropyl (meth)acrylate, (meth)acrylates [(mono-, di-, or poly-)alkylene glycol] esters such as (meth)acrylate mono(diethylene glycol) ester, and (meth)acrylate lactones such as (meth)acrylate monocaprolactone.

[0066] Examples of the amino group-containing monomer unit include repeating units derived from amino group-containing monomers such as (meth)acrylamide and allylamine.

[0067] Examples of the glycidyl group-containing monomer unit include repeating units derived from a glycidyl group-containing monomer such as glycidyl (meth)acrylate.

[0068] The content of the acrylic acid monomer units (a2) having a crosslinkable functional group in the acrylic polymer is preferably 0.01% to 40% by mass, and more preferably 0.5% to 35% by mass. By setting the content of the acrylic acid monomer units (a2) having a crosslinkable functional group within the above range, it is easy to control the crosslinking property and adhesiveness of the acrylic polymer.

[0069] Furthermore, when the acrylic acid monomer unit (a2) having a crosslinkable functional group is a carboxyl-containing monomer unit, the content of the carboxyl-containing monomer unit in the acrylic polymer is preferably 0.1% by mass or less, more preferably 0.05% by mass or less. The content of the carboxyl-containing monomer unit in the acrylic polymer is also preferably 0% by mass. By setting the content of the carboxyl-containing monomer unit to within the above range, a so-called acid-free adhesive sheet can be obtained. Thus, the discoloration resistance of the adhesive sheet can be more effectively improved.

[0070] The acrylic polymer may further contain a unit derived from an alkoxyalkyl-containing (meth)acrylate. The alkoxyalkyl-containing (meth)acrylate is an alkoxyalkyl (meth)acrylate. As the alkoxyalkyl (meth)acrylate, for example, preferably an alkoxyalkyl (meth)acrylate in which the number of carbon atoms of the alkoxy group is 1 to 12 and the number of carbon atoms of the alkylene group bonded to the alkoxy group is 1 to 18. The number of carbon atoms of the alkoxy group is preferably 1 to 8, more preferably 1 to 4, and particularly preferably 1 or 2. In addition, the number of carbon atoms of the alkylene group bonded to the alkoxy group is preferably 1 to 12, further preferably 1 to 8, further preferably 1 to 4, and particularly preferably 1 to 3.

[0071] Examples of such alkoxyalkyl (meth)acrylates include 2-methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxymethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate.

[0072] The acrylic polymer may further include units derived from nitrogen-containing monomers. Nitrogen-containing monomers are monomers containing nitrogen elements in one molecule. Examples of nitrogen-containing monomers include dimethylacrylamide, diethylacrylamide, acrylamide, hydroxyethylacrylamide, hydroxymethylacrylamide, methoxymethylacrylamide, ethoxymethylacrylamide, dimethylaminoethylacrylamide, N-vinylcaprolactam, N-vinyl-2-pyrrolidone, (methyl)dimethylaminoethyl acrylate, N-vinylformamide, etc. Among them, the nitrogen-containing monomer is preferably at least one selected from acrylamide derivatives, amino-containing monomers, and nitrogen-containing heterocyclic monomers, and more preferably acrylamide derivatives. Acrylamide derivatives are further preferably at least one selected from dimethylacrylamide, diethylacrylamide, and acrylamide, and dimethylacrylamide is particularly preferred.

[0073] The acrylic polymer may have other monomer units as required. Other monomers may be any monomers that can be copolymerized with the acrylic monomers, and examples thereof include (meth)acrylonitrile, vinyl acetate, styrene, vinyl chloride, vinyl pyrrolidone, vinyl pyridine, etc. The content of other monomer units in the acrylic polymer is preferably 20% by mass or less, and more preferably 15% by mass or less.

[0074] The acid value of the acrylic polymer is preferably 3 mgKOH / g or less, and further preferably 1 mgKOH / g or less, and particularly preferably 0.5 mgKOH / g or less. Furthermore, the acid value of the acrylic polymer may also be 0 mgKOH / g. By setting the acid value of the acrylic polymer within the range, the discoloration resistance of the adhesive sheet of the present invention can be more effectively improved.

[0075] The acid value of acrylic polymer is measured in accordance with JIS K 0070 (1992). Specifically, firstly, accurately weigh about 2 g of the sample in a 100 ml conical flask using a precision balance, and add 10 ml of a mixed solvent of ethanol / diethyl ether = 1 / 1 (weight ratio) to dissolve it. Furthermore, add 1 to 3 drops of phenolphthalein ethanol solution to the container as an indicator, and stir thoroughly until the sample is uniform. It is titrated using 0.1N potassium hydroxide-ethanol solution, and the neutralization endpoint is when the light red color of the indicator lasts for 30 seconds. The value obtained based on the result and using the following calculation formula (1) is set as the acid value of the acrylic polymer.

[0076] Acid value (mgKOH / g) = [B × f × 5.611] / S (1)

[0077] In the calculation formula (1), B is the amount of 0.1N potassium hydroxide-ethanol solution used (ml), f is the factor of 0.1N potassium hydroxide-ethanol solution, and S is the amount of acrylic acid polymer taken (g).

[0078] The weight average molecular weight of the acrylic polymer is preferably 100,000 to 2,000,000, and more preferably 200,000 to 1,500,000. Furthermore, the weight average molecular weight of the acrylic polymer is a value before crosslinking using a crosslinking agent described later. The weight average molecular weight is a value determined by size exclusion chromatography (SEC) based on a polystyrene standard. As the acrylic polymer, a commercially available one may be used, or one synthesized by a known method may be used.

[0079] (Colorant)

[0080] The adhesive sheet of the present invention includes a colorant. The colorant is preferably a black pigment, more preferably at least one selected from a metal oxide and carbon black, and further preferably a metal oxide, particularly preferably a black metal oxide. By using a black metal oxide as a colorant, the visibility of the adhesive sheet can be more effectively improved. In addition, by using a black metal oxide as a colorant, for example, when the adherend is a black frame, there is a tendency to further improve the sense of unity with the adherend. Furthermore, as a colorant, in addition to comprising a metal oxide, other colorants may also be included. As other colorants, for example, aniline black, activated carbon, carbon nanotubes, dyes, etc. can be cited.

[0081] Examples of the metal oxide include copper oxide, ferroferric oxide, manganese dioxide, titanium oxide, zinc oxide, zirconium oxide, barium titanate, potassium titanate, iron titanate, copper-chromium oxide, copper-manganese oxide, copper-iron-manganese oxide, copper-chromium-manganese oxide or copper-iron-chromium oxide, titanium black, etc. Among them, the metal oxide is more preferably a black metal oxide in which the metal species is selected from titanium, copper, iron and manganese, and further preferably a black metal oxide selected from copper, iron and manganese.

[0082] The lower limit of the primary average particle size of the colorant is not particularly limited, for example, preferably 0.01 μm or more. In addition, the primary average particle size of the metal oxide is preferably less than 5 μm, more preferably less than 1 μm, further preferably less than 0.5 μm, and particularly preferably less than 0.1 μm. By setting the primary average particle size of the metal oxide within the above range, the visibility of the adhesive sheet can be more effectively improved.

[0083] The content of the colorant is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and further preferably 0.2 parts by mass or more, relative to 100 parts by mass of the acrylic polymer. In addition, the content of the colorant is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less, relative to 100 parts by mass of the acrylic polymer.

[0084] The colorant is preferably mixed with the acrylic polymer in a state of being dispersed in a dispersion resin. Examples of the dispersion resin include polyester resins, urethane resins, acrylic resins, and polyether resins.

[0085] (Acid scavenger)

[0086] The adhesive sheet of the present invention preferably further comprises an acid scavenger. In this specification, the so-called acid scavenger refers to a cross-linked structure formed with the carboxyl group contained in the adhesive sheet. By allocating an acid scavenger in the adhesive sheet, the discoloration of the obtained adhesive sheet can be more effectively suppressed. Thus, the coloring of the adhesive sheet can be maintained even in a high temperature and high humidity environment.

[0087] As the acid scavenger, for example, compounds having an organic amino group, an oxaline group, an epoxy group, a carbodiimide group, etc. can be cited. Among them, the acid scavenger is preferably a compound having at least one selected from an oxazoline group and a carbodiimide group. By adding a compound having at least one selected from an oxazoline group and a carbodiimide group as an acid scavenger, the discoloration of the adhesive sheet can be more effectively suppressed.

[0088] Examples of compounds having an oxazoline group include 4,5-dihydro-2-(isopropenyl)oxazole-styrene polymers, ethyl / acrylate-2-isopropenyl-4,5-dihydro-1,3-oxazole-methyl / methacrylate polymers, butyl / acrylate-4,5-dihydro-2-(isopropenyl)oxazole-divinylbenzene-styrene polymers, etc. In addition, examples of compounds having a carbodiimide group include bis(2,6-diisopropylphenyl)carbodiimide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and 1,3-diisopropylcarbodiimide.

[0089] As a compound having an oxazoline group, a commercial product can be used. As a commercial product, Epocros RPS-1005 (manufactured by Japan Catalyst (Stock)), Epocros K-2000 series (manufactured by Japan Catalyst (Stock)), Epocros WK series (manufactured by Japan Catalyst (Stock)), 4,5-dihydro-β-methyl-2-oxazoleethanol (manufactured by Kawaguchi Chemical Industry (Stock)), etc. In addition, as a compound having a carbodiimide group, a commercial product can also be used. As a commercial product, cyclic carbodiimide "Carbosista" (manufactured by Teijin (Stock) Co., Ltd.), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (manufactured by Kawaguchi Chemical Industry (Stock) Co., Ltd., EDC), Carbodilite V-03 (manufactured by Nisshinbo Chemical (Stock) Co., Ltd.), etc.

[0090] The content of the acid scavenger is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, and further preferably 2 parts by mass or more, relative to 100 parts by mass of the acrylic polymer. In addition, the content of the acid scavenger is preferably 30 parts by mass or less, and more preferably 20 parts by mass or less, relative to 100 parts by mass of the acrylic polymer.

[0091] (Crosslinking agent)

[0092] The adhesive composition forming the adhesive sheet of the present invention may contain a crosslinking agent. The crosslinking agent may be suitably selected considering the reactivity of the crosslinking functional group possessed by the acrylic polymer. For example, the crosslinking agent may be selected from the known crosslinking agents such as isocyanate compounds, aziridine compounds, epoxy compounds, metal chelate compounds, butylated melamine compounds, etc. Furthermore, oxazoline compounds may be exemplified in the acid capture agent, but when the acrylic polymer has a carboxyl group, oxazoline compounds are sometimes used as crosslinking agents. However, when the acrylic polymer does not have a carboxyl group, oxazoline compounds do not function as crosslinking agents. That is, when the acrylic polymer does not have a carboxyl group, oxazoline compounds are not crosslinking agents, but function as acid capture agents. Similarly, when the acrylic polymer has a carboxyl group, carbodiimide compounds are sometimes used as crosslinking agents, but when the acrylic polymer does not have a carboxyl group, they are not used as crosslinking agents, so it is necessary to consider the reactivity of the crosslinking functional group possessed by the acrylic polymer to select a crosslinking agent.

[0093] As the crosslinking agent, an isocyanate compound is preferably used because the hydroxyl-containing (meth)acrylate can be easily crosslinked. The crosslinking agent is more preferably a difunctional or higher-functional isocyanate compound.

[0094] Examples of the isocyanate compound include toluene diisocyanate, xylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, etc. Examples of commercially available products include toluene diisocyanate compounds (Coronate L manufactured by Nippon Polyurethane Industries, Ltd.) and xylene diisocyanate compounds (Takenate D-110N manufactured by Mitsui Chemicals, Ltd.).

[0095] Examples of the epoxy compound include ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, tetraglycidyl xylene diamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, trimethylolpropane polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, and sorbitol polyglycidyl ether. Examples of commercially available products include 1,3-bis(N,N-diglycidylaminomethyl)benzene (Mitsubishi Gas Chemical Co., Ltd., TETRAD-X), 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (Mitsubishi Gas Chemical Co., Ltd., TETRAD-C), and the like.

[0096] The content of the crosslinking agent in the adhesive composition can be appropriately selected according to the desired adhesion, but is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the acrylic polymer. By setting the content of the crosslinking agent within the range, the processability can be further improved. Furthermore, as a crosslinking agent, one can be used alone or two or more can be used in combination. When two or more are used in combination, it is preferred that the total mass is within the range.

[0097] (Ultraviolet light absorber)

[0098] The adhesive sheet of the present invention may contain an ultraviolet absorber. The ultraviolet absorber may be selected from those having a maximum absorption wavelength in the ultraviolet region. In the present invention, an ultraviolet absorber having a maximum absorption wavelength above 350 nm may be used. As an ultraviolet absorber having a maximum absorption wavelength above 350 nm, for example, a compound represented by the following general formula (1) or general formula (2) may be cited.

[0099] [Chemistry 1]

[0100] General formula (1)

[0101]

[0102] In the above formula, R 1 represents a hydrogen atom, a halogen atom, an alkoxy group having 1 to 4 carbon atoms, a nitro group or a cyano group, and R 2 represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 3 It represents an alkyl structure.

[0103] [Chemistry 2]

[0104] General formula (2)

[0105]

[0106] In the above formula, R 4 , R 5 and R 6 is a hydrogen atom, a hydroxyl group, an alkyl structure or a halogen atom, and R is absent. 4 , R 5 and R 6 The alkyl structure is a concept including a substituent mainly composed of an alkyl group, such as a substituted or unsubstituted alkyl group or a substituted or unsubstituted alkoxy group.

[0107] Among them, it is particularly preferable to use a UV absorber that has improved compatibility by introducing a large molecular weight alkyl group into the aromatic ring of the basic skeleton and is liquid or oily at 23° C. Here, liquid or oily at 23° C. means that the UV absorber has fluidity even without a diluent solvent.

[0108] As the ultraviolet absorber, a commercially available product may be used. Examples of the commercially available product include triazine ultraviolet absorbers (Tinuvin 477) and benzotriazole ultraviolet absorbers (Tinuvin 109, Tinuvin 384-2, Tinuvin PS) manufactured by BASF Japan.

[0109] The content of the ultraviolet absorber is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and further preferably 6 parts by mass or less relative to 100 parts by mass of the acrylic polymer. The content of the ultraviolet absorber in the present invention is preferably adjusted to an amount in which the ultraviolet transmittance at a wavelength of 380 nm is less than 10%. That is, the ultraviolet transmittance of the adhesive sheet of the present invention at a wavelength of 380 nm is preferably less than 10%. The ultraviolet absorber may be used alone or in combination of two or more. In the case of using two or more in combination, the total mass is preferably within the range.

[0110] (Solvent)

[0111] The adhesive composition forming the adhesive sheet of the present invention may contain a solvent. In such a case, the solvent is used to improve the coating suitability of the adhesive composition. Examples of the solvent include hydrocarbons such as hexane, heptane, octane, toluene, xylene, ethylbenzene, cyclohexane, and methylcyclohexane; halogenated hydrocarbons such as dichloromethane, trichloroethane, trichloroethylene, tetrachloroethylene, and dichloropropane; alcohols such as methanol, ethanol, propanol, isopropyl alcohol, butanol, isobutyl alcohol, and diacetone alcohol; ethers such as diethyl ether, diisopropyl ether, dioxane, and tetrahydrofuran; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, isophorone, and cyclohexanone; esters such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, amyl acetate, and ethyl butyrate; polyols such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monomethyl ether acetate, and their derivatives.

[0112] The content of the solvent in the adhesive composition is not particularly limited, but is preferably 25 to 500 parts by mass, more preferably 30 to 400 parts by mass, based on 100 parts by mass of the acrylic polymer.

[0113] The content of the solvent is preferably 10% to 90% by mass, more preferably 20% to 80% by mass, relative to the total mass of the adhesive composition. The solvent may be used alone or in combination of two or more. When two or more solvents are used in combination, the total mass is preferably within the above range.

[0114] (Other ingredients)

[0115] The adhesive sheet may contain other ingredients other than those described above within the scope of not impairing the effects of the present invention. As other ingredients, known ingredients as adhesive additives can be cited. For example, it can be selected from plasticizers, antioxidants, metal corrosion inhibitors, adhesion imparting agents, silane coupling agents, hindered amine compounds and other light stabilizers as needed.

[0116] Examples of the plasticizer include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristic acid, vinyl palmitic acid, vinyl stearate, vinyl cyclohexanecarboxylate, vinyl carboxylate such as vinyl benzoate, and vinyl esters of carboxylic acids; and styrene.

[0117] Examples of the antioxidant include phenolic antioxidants, amine antioxidants, lactone antioxidants, phosphorus antioxidants, sulfur antioxidants, etc. These antioxidants may be used alone or in combination of two or more.

[0118] As the metal corrosion inhibitor, benzotriazole-based resins are preferred examples in terms of compatibility with the adhesive and high degree of effect.

[0119] Examples of the tackifier include rosin-based resins, terpene-based resins, terpene-phenol-based resins, coumarone-indene-based resins, styrene-based resins, xylene-based resins, phenol-based resins, and petroleum resins.

[0120] Examples of the silane coupling agent include mercaptoalkoxysilane compounds (eg, mercapto-substituted alkoxy oligomers).

[0121] (Method for producing adhesive sheet)

[0122] The method for producing an adhesive sheet of the present invention preferably includes a step of applying an adhesive composition on a release sheet to form a coating film.

[0123] The adhesive composition can be applied using a known coating device, such as a blade coater, an air knife coater, a roll coater, a rod coater, a gravure coater, a micro gravure coater, a rod blade coater, a lip coater, a die coater, a curtain coater, etc.

[0124] The method for producing an adhesive sheet preferably includes a step of heating the coating film. In this case, when heating the coating film formed by applying the adhesive composition, a known heating device such as a heating furnace or an infrared lamp can be used.

[0125] Furthermore, the adhesive sheet preparation agent may be subjected to an aging treatment by leaving the adhesive sheet at a certain temperature for a certain period of time after the solvent is removed after coating. The aging treatment may be performed, for example, by leaving the adhesive sheet at 23° C. for 7 days.

[0126] (Application of adhesive sheet)

[0127] The adhesive sheet of the present invention is used for bonding transparent components. Among them, the adhesive sheet of the present invention is preferably used for bonding optical components. As optical components, various structural components in optical products such as touch screens or image display devices or anti-scattering films bonded to the cover glass (cover lens) of the outermost layer can be listed. Among them, it is preferably used as a touch screen bonded to the adhesive sheet of the present invention. As a structural component of the touch screen, for example, an ITO film (film) having an ITO film on a transparent resin film, an ITO glass having an ITO film on the surface of a glass plate, a transparent conductive film coated with a conductive polymer on a transparent resin film, a hard coating, a fingerprint-resistant film, etc. As a structural component of an image display device, for example, anti-reflection films, orientation films, polarizing films, phase difference films, brightness enhancement films, etc. used in liquid crystal display devices can be listed.

[0128] Examples of materials used for these members include glass, polycarbonate, polyethylene terephthalate, polymethyl methacrylate, polyethylene naphthalate, cycloolefin polymers, triacetyl cellulose, polyimide, and cellulose acylate. The adhesive sheet of the present invention can be particularly preferably used for bonding to glass.

[0129] The present invention may also relate to a laminated body formed by laminating the adhesive sheet and the transparent member. In the case of manufacturing the laminated body, the step of laminating the adhesive sheet to the transparent member is included. In the laminating step, the adhesive sheet is preferably laminarized to the transparent member using a manual roller or the like. In addition, in order to improve the adhesion between the adhesive sheet and the transparent member, for example, an autoclave treatment may be performed under the conditions of 20°C to 100°C and 1 atmosphere to 10 atmospheres.

[0130] (Laminated body)

[0131] The present invention also relates to a laminate having a surface layer on one side of the transparent member laminating adhesive sheet and a display body on the other side. That is, the laminate has a surface layer, a transparent member laminating adhesive sheet and a display body in sequence. In the laminate, other layers may be provided between the surface layer and the transparent member laminating adhesive sheet, or between the transparent member laminating adhesive sheet and the display body, but in one embodiment, the structure is as follows: the surface layer, the transparent member laminating adhesive sheet and the display body are directly laminated in sequence, and no other layers are provided between the structures.

[0132] The surface layer is a layer provided on the outermost surface of the laminate, and for example, when the laminate is incorporated into a display, the surface layer is a layer provided on the outermost surface of the visible side. The surface layer may be a surface protection film or a decorative film.

[0133] The surface layer is preferably a glass layer or a resin layer. The glass layer is not particularly limited, and examples thereof include chemically strengthened glass, alkali-free glass, quartz glass, soda-lime glass, glass containing barium and strontium, aluminum silicate glass, lead glass, borosilicate glass, and barium borosilicate glass. The resin layer is not particularly limited, and examples thereof include acrylic plates containing polymethyl methacrylate and the like, polycarbonate plates, and the like. Among them, the surface layer is more preferably a glass layer.

[0134] The surface layer may have a step on at least one side. For example, a frame-shaped step may be provided on the side where the adhesive sheet of the surface layer is bonded. In the case described above, the thickness of the step may be 1 μm to 50 μm, 5 μm to 40 μm, or 10 μm to 30 μm. In addition, the thickness of the step is preferably 50% or less, more preferably 40% or less, and further preferably 30% or less relative to the thickness of the adhesive sheet. By setting the step provided in the surface layer to the conditions described above, it is possible to suppress the generation of floating or bubbles in the step portion between the adhesive layer including the adhesive sheet and the surface layer, and the laminate can exhibit excellent design properties.

[0135] Furthermore, a functional layer such as a hard coat layer, an antireflection layer, or an antiglare layer may be provided on one or both sides of the surface layer.

[0136] Examples of the display include a liquid crystal (LCD) module, a light emitting diode (LED) module, an organic electroluminescence (organic EL (electroluminescence)) module, and electronic paper.

[0137] [Example]

[0138] The following examples and comparative examples are listed to more specifically illustrate the features of the present invention. The materials, usage amounts, ratios, processing contents, processing sequences, etc. shown in the following examples may be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention should not be construed in a limited manner by the specific examples shown below.

[0139] <Synthesis of Acrylic Polymer A>

[0140] Acrylic polymer A was prepared by solution polymerization in ethyl acetate. In ethyl acetate, butyl acrylate (BA) and 2-hydroxyethyl acrylate (2HEA) were mixed in a mass ratio of 70:30, and azobisisobutyronitrile (AIBN) as a free radical polymerization initiator was dissolved in the solution. The solution was heated to 60°C for random copolymerization to obtain acrylic polymer A. The solution viscosity of a 35% by mass solution of the acrylic polymer A at 23°C was 6,400 mPa·s. In addition, the acid value of acrylic polymer A was 0.2 mgKOH / g.

[0141] <Synthesis of Acrylic Polymer B>

[0142] In ethyl acetate, butyl acrylate (BA), methyl acrylate (MA), lauryl acrylate (LA) and 2-hydroxyethyl acrylate (2HEA) were prepared in a mass ratio of 35:30:10:25, and azobisisobutyronitrile (AIBN) as a free radical polymerization initiator was dissolved in the solution. The solution was heated to 60°C for random copolymerization to obtain acrylic polymer B. The solution viscosity of a 45% by mass solution of the acrylic polymer B at 23°C was 5,600 mPa·s. In addition, the acid value of the acrylic polymer B was 0.3 mgKOH / g.

[0143] (Example 1)

[0144] Acrylic polymer A, an ethyl acetate solution of toluene diisocyanate adduct of trimethylolpropane (Coronate L-55E, manufactured by Tosoh Corporation), a copper, iron, manganese oxide pigment (TM Black 3550, manufactured by Dainichi Seika Industries, Ltd.), an acid scavenger (bis(2,6-diisopropylphenyl)carbodiimide) and ethyl acetate as a solvent were mixed to obtain an adhesive composition having a solid content concentration of 30% by mass and containing 0.5 parts by mass of a crosslinking agent, 0.03 parts by mass of a metal oxide, and 5 parts by mass of an acid scavenger relative to 100 parts by mass of the acrylic polymer A.

[0145] The adhesive composition was applied to a first release sheet (a heavy release film, a polyethylene terephthalate film produced by Teijin DuPont Films Co., Ltd., and subjected to a demolding treatment). The coating was performed using a YD-type scraper produced by Yoshimitsu Seiki Co., Ltd., in such a manner that the thickness after drying was 250 μm. Thereafter, the adhesive sheet having an adhesive layer was formed by drying at 100° C. for 3 minutes using a hot air dryer to remove the solvent.

[0146] A second release sheet (light release film, manufactured by Teijin DuPont Films Co., Ltd.) subjected to a release treatment and having a higher single-sided releasability than the first release sheet was attached to the pressure-sensitive adhesive sheet to obtain a pressure-sensitive adhesive sheet with a release sheet, i.e., the pressure-sensitive adhesive sheet of Example 1.

[0147] (Example 2)

[0148] Acrylic polymer B, ethyl acetate solution of xylene diisocyanate compound (Takenate D-110N manufactured by Mitsui Chemicals Co., Ltd.), copper, iron, manganese oxide pigment (TM Black 3550 manufactured by Dainichi Seika Industries Co., Ltd.), acid scavenger (bis(2,6-diisopropylphenyl)carbodiimide) and ethyl acetate as solvent were mixed to obtain an adhesive composition containing 0.3 parts by mass of a crosslinking agent, 0.03 parts by mass of a metal oxide, 5 parts by mass of an acid scavenger, and a solid content concentration of 40% by mass relative to 100 parts by mass of acrylic polymer B. Using the adhesive composition, an adhesive sheet with a release sheet was obtained in the same manner as in Example 1.

[0149] (Example 3)

[0150] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 1 except that the acid scavenger was changed to 5 parts by mass of oxazoline (manufactured by Nippon Catalyst Co., Ltd., Epocros RPS-1005), the metal oxide was changed to 0.15 parts by mass, and the thickness of the adhesive sheet was changed to 100 μm.

[0151] (Example 4)

[0152] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 1 except that the content of the metal oxide was changed to 0.23 parts by mass based on 100 parts by mass of the acrylic polymer A and the thickness of the adhesive sheet was changed to 150 μm.

[0153] (Example 5)

[0154] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 1 except that the metal oxide was changed to 0.25 parts by mass of a titanium oxide pigment (MHI Black #PD-367M manufactured by Mikoku Pigments Co., Ltd.) and the thickness of the adhesive sheet was changed to 200 μm.

[0155] (Example 6)

[0156] The metal oxide was changed to carbon black pigment (Toyo Color Co., Ltd., Multilac A 903 Black), and the amount of the pigment was changed to 0.80 parts by mass. Furthermore, the thickness of the adhesive sheet was changed to 50 μm, and an adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 2.

[0157] (Comparative Example 1)

[0158] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 1 except that the acid scavenger was not added.

[0159] (Comparative Example 2)

[0160] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 2 except that the acid scavenger was not added.

[0161] (Comparative Example 3)

[0162] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 3 except that the acid scavenger was not added.

[0163] (Comparative Example 4)

[0164] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 4 except that the acid scavenger was not added.

[0165] (Comparative Example 5)

[0166] Furthermore, an adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Comparative Example 3 except that no metal oxide was added.

[0167] (Measurement and evaluation)

[0168] <Total light transmittance>

[0169] The adhesive film was cut into a size of 50 mm wide and 50 mm long, and the light peeling separator as the second peeling sheet was peeled off and attached to a glass slide (S9112 manufactured by Matsunami Glass Co., Ltd.) using a manual roller. Then, the first peeling sheet was peeled off and the exposed adhesive surface was attached to another glass slide using a laminator. In this state, it was kept in an autoclave at 40°C and 5 atmospheres for 30 minutes to adhere to the glass plate.

[0170] For the obtained laminate, in accordance with JIS K 7150, the total light transmittance was measured using an integrating sphere type light transmittance measuring device (manufactured by Nippon Denshoku Industries Co., Ltd., NDH-5000). The measurement was performed three times in the central region of the sample, and the average value was set as the total light transmittance of the adhesive sheet.

[0171] <Change amount of total light transmittance>

[0172] A sample prepared in the same manner as the measurement of <total light transmittance> was placed in an environment of 85 °C and 85% relative humidity, and the total light transmittance after 500 hours was measured. Furthermore, based on the total light transmittance of the sample before being placed in the environment of 85 °C and 85% relative humidity, the change amount was calculated using the following formula and evaluated according to the following evaluation criteria.

[0173] Change amount (%) = (Total light transmittance of the sample before treatment) - (Total light transmittance of the sample after treatment)

[0174] <Decolorization resistance>

[0175] For a sample prepared in the same manner as the measurement of <total light transmittance>, in accordance with JIS Z8781-4, the L* value in the L*a*b* color space was measured using a color measuring device (manufactured by Suga Test Instruments Co., Ltd., Colour Cute i). The measurement was performed three times in the central region of the sample, and the average value was set as the L* value of the adhesive sheet.

[0176] <Change amount of L*>

[0177] A sample prepared in the same manner as the measurement of <total light transmittance> was placed in an environment of 85 °C and 85% relative humidity, and the L* value after 500 hours was measured. Furthermore, based on the L* value of the sample before being placed in the environment of 85 °C and 85% relative humidity, the change amount was calculated using the following formula and evaluated according to the following evaluation criteria.

[0178] Change amount = (L* value of the sample before treatment) - (L* value of the sample after treatment)

[0179] A: The change amount of the L* value is less than 1.0, and the total light transmittance after treatment is less than 85%

[0180] B: The change amount of the L* value is 1.0 or more and less than 2.0, and the total light transmittance after treatment is less than 85%

[0181] C: The change amount of the L* value is 2.0 or more, or the total light transmittance after treatment is 85% or more

[0182] <Design>

[0183] A sample was prepared in the same manner as in the measurement of <Total Light Transmittance>, placed on a liquid crystal display showing a black screen, and visually evaluated.

[0184] A: It looks darker than when nothing is loaded

[0185] B: No change

[0186] <Sense of unity>

[0187] Ultraviolet curable black ink was screen-printed on the surface of a glass plate (120 mm long x 70 mm wide x 0.7 mm thick) in a frame shape (inner edge dimensions: 90 mm long x 50 mm wide x 5 mm wide) so that the coating thickness became 5 μm, thereby obtaining a printed step glass plate with a step difference of 5 μm.

[0188] Then peel off the first peeling sheet of the adhesive sheet with a peeling sheet cut into 90mm in length and 54mm in width, and use a manual roller to adhere to a PET film (manufactured by Toyobo, Cosmoshine A4300#100) to make a laminated film. The laminated film is cut into 95mm in length and 55mm in width, and the second peeling sheet is peeled off, and the exposed adhesive surface is adhered to a glass plate (surface layer) with a printed step difference. At this time, a manual roller is used to adhere in a manner that the adhesive sheet covers the entire printed surface on the frame edge. In the above state, keep it in an autoclave at 40°C and 5 atmospheres for 30 minutes and perform close contact.

[0189] In this state, the film was placed on a liquid crystal display showing a black screen with the glass surface facing upward and the adhesive sheet surface facing downward, and visual evaluation was performed.

[0190] A: The black screen and the surrounding black printing (black printing in the form of a frame) appear to be one piece.

[0191] B: The boundary between the black screen and the surrounding black print (frame-shaped black print) looks blurred

[0192] C: The boundary between the black screen and the surrounding black print (frame-shaped black print) looks clear

[0193] [Table 1]

[0194]

[0195] The adhesive sheets obtained in Examples are excellent in discoloration resistance. In addition, the adhesive sheets obtained in Examples are also excellent in design properties.

[0196] <Production of Laminated Body>

[0197] Two polarizing plates with adhesive layers (manufactured by Polatechno (stock), SKN-18243T-HC) were bonded via an adhesive layer in such a way that the polarization axis was in an orthogonal Nicol state (polarization axis: ∠45°, ∠135°) to produce a first laminate comprising polarizing plate / adhesive layer / polarizing plate / adhesive layer / diaphragm. Subsequently, a first glass plate (120 mm in length × 70 mm in width × 0.7 mm in thickness) was bonded to the adhesive layer exposed by peeling off the diaphragm of the first laminate to produce a second laminate comprising polarizing plate / adhesive layer / polarizing plate / adhesive layer / first glass plate. Furthermore, the two polarizing plates were configured in an orthogonal Nicol state and were therefore in an extinction state.

[0198] Then, the adhesive sheet obtained in the embodiment is cut into 90 mm in length and 54 mm in width, the first peeling sheet is peeled off, and a manual roller is used to adhere to the polarizing plate side (surface polarizing plate side) of the second laminate, thereby producing a third laminate (diaphragm / adhesive sheet (adhesive layer) obtained in the embodiment / polarizing plate / adhesive layer / polarizing plate / adhesive layer / first glass plate). Then, the adhesive surface exposed after peeling off the heavy peeling sheet is adhered to a glass plate (surface layer) with a printing step difference produced by the method described later. At this time, a manual roller is used to adhere the adhesive sheet in such a way that the entire printed surface on the frame edge is covered. In the described state, the adhesive sheet is kept in an autoclave at 40°C and 5 atmospheres for 30 minutes and is in close contact. In this way, a laminated body having a surface layer, an adhesive sheet for bonding a transparent component, and a display body in sequence is obtained (glass plate with printed step difference / adhesive sheet (adhesive layer) obtained in the embodiment / polarizing plate / adhesive layer / polarizing plate / adhesive layer / first glass plate).

[0199] Furthermore, the glass plate (surface layer) with a printed step difference is obtained by screen printing ultraviolet curable black ink on the surface of a glass plate (120 mm long × 70 mm wide × 0.7 mm thick) in a frame shape (inner edge dimensions: 90 mm long × 50 mm wide × 5 mm wide) in a manner such that the coating thickness becomes 5 μm, thereby forming a step difference of 5 μm.

[0200] The adhesive sheets obtained in Examples had excellent sense of unity even when formed into the above-mentioned laminated body.

Claims

1. An adhesive sheet for bonding a transparent member, comprising an acrylic polymer and a colorant, wherein the adhesive sheet for bonding a transparent member further comprises an acid scavenger. The acid scavenger is a compound having at least one selected from an oxazoline group and a carbodiimide group, The content of carboxyl group-containing monomer units in the acrylic polymer is 0.1 mass % or less, When the adhesive sheet for laminating a transparent member was sandwiched between two glass plates and stored for 500 hours in an environment of 85° C. and a relative humidity of 85%, the change in total light transmittance was less than 2%. 2 . The adhesive sheet for bonding a transparent member according to claim 1 , wherein the colorant is a black metal oxide. 3 . The adhesive sheet for bonding a transparent member according to claim 1 , wherein the total light transmittance is 30% or more and less than 85%. 4 . The adhesive sheet for bonding a transparent member according to claim 1 , wherein a primary average particle size of the colorant is 0.01 μm or more and less than 5 μm. 5 . A laminated body comprising a surface layer on one side of the pressure-sensitive adhesive sheet for laminating a transparent member according to claim 1 , and a display body on the other side. The laminated body according to claim 5 , wherein the surface layer is a glass layer or a resin layer.

Citation Information

Patent Citations

  • Double-sided pressure-sensitive adhesive sheet

    JP2005060435A

  • Black foil-like adhesive and black adhesive sheet

    JP2013032430A

  • Double-sided adhesive sheet and optical member

    CN106170522A

  • Adhesive sheet and display body

    CN110713799A

  • Double-coated tape and liquid crystal display module unit using same

    JP2006010931A